2008
DOI: 10.1620/tjem.215.71
|View full text |Cite
|
Sign up to set email alerts
|

School Children's Salt Intake Is Correlated with Salty Taste Preference Assessed by Their Mothers

Abstract: Salt intake in childhood is a risk factor for developing hypertension later in life. As health education for children to decrease salt intake, it is important for them to know the relationship between salty taste preference and salt intake. The objective of this study was to investigate the relationship between children's salty taste preference and their salt intake. We employed a cross-sectional study design, and the subjects were 199 elementary school children (5th or 6th grade) and their mothers. The amount… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 16 publications
0
14
0
2
Order By: Relevance
“…2). Generally, saltiness is associated with overall preference in food, and people tend to prefer food with a higher salt content (Matsuzuki et al , 2008). For oiliness values, the cheese made with the double emulsions differed significantly from the cheese made without the emulsions, perhaps due to the MCT oil in the emulsions.…”
Section: Resultsmentioning
confidence: 99%
“…2). Generally, saltiness is associated with overall preference in food, and people tend to prefer food with a higher salt content (Matsuzuki et al , 2008). For oiliness values, the cheese made with the double emulsions differed significantly from the cheese made without the emulsions, perhaps due to the MCT oil in the emulsions.…”
Section: Resultsmentioning
confidence: 99%
“…Despite these limitations, the current study is important in demonstrating that a streamlined, brief intervention in schools can impart a practical skill related to food choice to students and their parents. The influence of a school‐based program on knowledge in parents was especially gratifying, as dietary behavior is apt to be a matter of familial choice 33,34 . Further study will be required to verify that this intervention can lead to improvements in actual dietary pattern and related health measures, over time.…”
Section: Resultsmentioning
confidence: 99%
“…The optimal salinity revealed by the hedonic rating was higher than the optimal level revealed by the intake data [14]. A study of 10- to 12-year-old children showed that those who liked salty foods (as reported by their mother) ingested more salt (as estimated by urinary sodium excretion) [15]. Another study showed a positive effect of salt content on food intake in 2- to 3-year-olds [16].…”
Section: Introductionmentioning
confidence: 99%